Transthyretin amyloidosis: a phenocopy of hypertrophic cardiomyopathy. (3rd April 2017) - Vermeer, Alexa M. C.; Janssen, Anneloes; Boorsma, Peter C.; Mannens, Marcel M. A. M.; Wilde, Arthur A. M.; Christiaans, Imke
Abstract: Objectives: Hypertrophic cardiomyopathy (HCM) is an inherited cardiac disorder that affects over one in 500 persons worldwide. The autosomal dominant transmission of HCM implies that many relatives are at risk for HCM associated morbidity and mortality, therefore genetic testing and counselling is of great importance. However, in only 50–60% of the patients a mutation is found, which hampers predictive genetic testing in relatives. In HCM patients in whom the causal mutation has not been identified (yet), phenocopies of HCM – i.e. diseases that mimic HCM – could be responsible for the HCM phenotype. One of the HCM phenocopies is transthyretin amyloidosis (ATTR), caused by mutations in the transthyretin ( TTR ) gene. Methods: From 697 HCM index patients referred to our cardiogenetics outpatient clinic and tested for HCM associated genes between January 1997 and December 2012, we selected the ones without a detected causal mutation ( n  = 345). In these patients, additional DNA analysis of the TTR gene was performed. Results: In four patients (1.2%), a TTR mutation was detected (E7G, V30M, T119M, V122I). The E7G mutation is probably a non-pathogenic mutation. The T119M mutation is a known TTR mutation, but does not cause a cardiac phenotype. So in two (0.6%) patients, TTR analysis identified the cause of their HCM. Conclusions: ATTR should always be considered in patients with unexplained HCM, especially because of the great benefit of an early diagnosis regarding treatment and prognosis.